LEGAL TRANSLATION TRAINING IN POLAND: THE PROFESSION’S STATUS, EXPECTATIONS, REALITY AND PROGRESS TOWARDS (PROSPECTIVE) EXPERTISE? - KOŚCIAŁKOWSKA-OKOŃSKA, Ewa (Comparative Legilinguistics, 2014)
The paper addresses the field of translating legal texts (from Polish into English and from English into Polish) from the point of view of translation teaching and skill development. Due to the changing perspective of the translator’s profession, the necessity has emerged to have a closer look at the way translation skills and competence are developed and how the objective of such training is perceived by users (trainees). The results of a survey (conducted among trainees prior to the course and as a follow-up) are presented; the survey was aimed at juxtaposing expectations expressed by trainees with their follow-up achievements. It was assumed that trainees’ awareness of potential competence-related problem areas (i.e. to underline the significance of such extralinguistic concepts as, e.g., background knowledge or cognitive factors) should be increased, combined with the responsibility for tasks performed as active participants of translation interactions. The complexity of competence, problems with defining the nature of expertise and its applicability to the research context as well as the significance of the didactic process still remain worthy objectives of further research. Trainees should be also made aware of changing market requirements and expectations as to skills and qualifications they should have to be highly appreciated and competitive employees.